The crafty opponent: the defense systems of Staphylococcus aureus and response measures - Hou, Hongjie; Li, Yang; Jin, Yuefei; Chen, Shuaiyin; Long, Jinzhao; Duan, Guangcai; Yang, Haiyan (Folia microbiologica, 2022)
Staphylococcus aureus is a serious threat to public health. S. aureus infection can cause acute or long-term persistent infections that are often resistant to antibiotics and are associated with high morbidity and death. Understanding the defensive systems of S. aureus can help clinicians make the best use of antimicrobial drugs and can also help with antimicrobial stewardship. The mechanisms and clinical implications of S. aureus defense systems, as well as potential response systems, were discussed in this study. Because resistance to all currently available antibiotics is unavoidable, new medicines are always being developed. Alternative techniques, such as anti-virulence and bacteriophage therapies, are being researched and may become major tools in the fight against staphylococcal infections in the future, in addition to the development of new small compounds that affect cell viability.
Keywords: virulence; Methicillin-Resistant Staphylococcus aureus; Staphylococcal Infections; Virulence; Anti-Bacterial Agents; Humans; stafylokokové infekce; Staphylococcus aureus; lidé; antibakteriální látky; methicilin rezistentní Staphylococcus aureus